Features of the Occurrence of Ore at Red Mountain, Ouray County, Colo. - T. E. SCHTVARZ (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1905)
THE publication of the report by Mr. F. L. Ransome was welcomed by many engineers who had mined in the heart of the Sail Juan country, braved its long and snowy winters, climbed its lofty peaks, run the gauntlet of its snow-slides, and studied its problems of geology, while making dividends for their English or American clients. This report helps one to understand why the bonanzas occurred, and why the inevitable borrasca presents itself where least expected. The Red Mountain district of Ouray county, a very productive section from 1884 to 1893, occupies considerable space in the report mentioned.. The character of the ore-occurrence, being distinctive and presenting many features not existing elsewhere, has been deserving of special study. It is to be regretted that Mr. Ransome was .unable to observe the conditions underground, as all the principal properties, many of which I opened and developed, were closed at the time of his investigation: It has been my privilege to have contributed a few brief papers recording my observations in developing these properties ; and it is the object of the present paper to present certain sections of the Yankee Girl mine, which throw additional light on the geology of the section and make the available data more complete. The main Yankee Girl chimney or " stock" was the most productive for the first 500 ft. in depth of any chimney in the district.